Nutritional problems in children Efektivitas Pemberian Makanan Tambahan Terhadap Perbaikan Status Gizi Balita di Desa Jambugeulis: Studi Kuasi-Eksperimen - Sela Amelia Sela; Dani Nurdiansyah; Sinti Selpiah; Disva Nindia Desvande; Teguh Bilal Nurdian Billah; Siti Kokom Komariah; Fajar Nurohman (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Nutritional problems in children are one of the critical health issues, particularly in rural areas. This study aims to evaluate the effectiveness of Supplementary Feeding (PMT) in improving the nutritional status of children in Jambugeulis Village. This research employs a quasi-experimental method with a pretest-posttest design on 7 children with malnutrition problems. Nutritional status was measured based on Weight-for-Age (BB/U) and Weight-for-Height (BB/TB) indicators before and after PMT intervention for 28 days. The data were analyzed using paired t-test. The results showed a significant improvement in the children's nutritional status after the intervention, where the average z-score of BB/U increased from -3.13 to -2.54, and the z-score of BB/TB improved from -2.86 to -2.08. All participating children experienced an improvement in their nutritional status. The conclusion of this study is that PMT is proven to be effective in enhancing the nutritional status of children with malnutrition in Jambugeulis Village.